Real-time tracking of curing process of an epoxy adhesive by X-ray photon correlation spectroscopy - Tsapatsaris, Leonidas; Wiegart, Lutz; Petrash, Stanislas; Baumeister, Tobias; Engels, Thomas; Endoh, Maya; Koga, Tadanori (Frontiers in Soft Matter, 2024)
Introduction: Cross-linkable polymers are in widespread use in a variety of industries because of their thermomechanical toughness, chemical resistance, and adhesive strength. But traditional methods to characterize these materials are insufficient for fully capturing the complex chemical and physical mechanisms of the crosslinking reaction. In this study, in situ X-ray photon correlation spectroscopy (XPCS) was used to investigate the crosslinking kinetics of a two-component epoxy resin adhesive. Materials and methods: With XPCS, we tracked the temporally resolved dynamics of silica filler particles, which served as probes of the internal dynamics of the thermoset network and allowed us to study the crosslinking process. The epoxy was cured isothermally at 40 °C and 80 °C to study the effects of curing temperature on the epoxy’s crosslinking reaction. XPCS results were compared to dielectric analysis (DEA) results, to demonstrate the similarities between a traditional technique and XPCS, and highlight the additional information gained with XPCS. Results and discussion: The epoxy resin was found to be highly sensitive to temperature. The epoxy samples exhibited different relaxation processes depending on isothermal cure temperature, indicating a complex relationship between applied temperature and the development of stress/relaxation conditions associated with formation of the thermoset network. Heating to the isothermal temperature setpoint at the start of curing promoted gelation, but the vitrification process was not completed during the isothermal curing stage. Instead, cooling the sample to room temperature facilitated the final vitrification process. This paper contextualizes this epoxy’s results within the broader field of thermoset study via XPCS, and advocates for XPCS as a fundamental technique for the study of complex polymers.